Communicating the unknown: descriptions of pictured scenes and events presented on video by children and adolescents using aided communication and their peers using natural speech - Murray, Janice; Sandberg, Annika Dahlgren; Smith, Martine M.; Deliberato, Debora [UNESP]; Stadskleiv, Kristine; von Tetzchner, Stephen (Taylor & Francis Ltd, 2018)
The facility to describe scenes and events is important in everyday communication, but little is known about the description skills and strategies of young people using aided communication. This article explores how 81 children and adolescents using aided communication and 56 peers using natural speech, aged 5-15 years, described pictured scenes and events presented on video to a partner who had no prior knowledge of the content. The group who used aided communication took longer and included fewer elements in their descriptions than the reference group; however, the groups did not differ in their use of irrelevant or incorrect elements, suggesting that both groups stayed on topic. Measures related to aided message efficiency correlated significantly with measures of spoken language comprehension. There were no significant differences between groups for their descriptions of pictured scenes and video events. Analyses showed both unpredicted group similarities and predictable differences, suggesting key components for future research consideration.
Keywords: Aided language; peers; pictured scenes; video events; co-construction